Teacher Readiness and School Infrastructure in Implementing AI Integrated Programming Learning in Junior High School: A Systematic Literature Review - Alnawati Alnawati (Journal of Innovation in Teaching and Instructional Media, 2026)
This study systematically analyses teacher readiness and school infrastructure for implementing AI-integrated programming learning in junior high schools. A Systematic Literature Review (SLR) was conducted following PRISMA guidelines, synthesizing 15 peer-reviewed articles published between 2021 and 2026. The findings reveal that teacher readiness is the most critical factor, with synthesized evidence indicating that fewer than one-third of teachers report adequate AI training, accompanied by concerns about role replacement and a gap between basic digital literacy and specific AI literacy. Infrastructure challenges include a significant digital divide between OECD and non-OECD countries and an urgent need for policy frameworks governing data privacy and ethical AI use in schools. The review also identifies a contradiction in the literature between technological optimism and socio-cultural resistance among educators. The study concludes that successful AI integration requires a holistic approach encompassing continuous teacher professional development, equitable infrastructure distribution, and systemic policies supporting ethical and inclusive pedagogical transformation.